Rapid cochlear gene therapy in adult deaf mice: Vglut3 rescue via AAV8 achieves day-1 hearing restoration - Ting Zhang; Rongqun Zhai; Mengli Liu; Hongen Xu; Liang Wang; Wenxue Tang; Bei Chen; Xingle Zhao (Molecular Therapy: Methods & Clinical Development, 2025)
Genetic hearing loss, caused by mutations in critical auditory genes, has seen promising advances through gene therapy, yet the temporal dynamics of early-stage auditory functional recovery and therapeutic transgene expression patterns following intervention remain uncharacterized in preclinical deafness models. This study systematically investigates the post-treatment progression of cochlear functional restoration and spatially resolved transgene expression kinetics in adult Vglut3 knockout (Vglut3KO) mice following adeno-associated virus (AAV)-mediated inner ear gene therapy. AAV8 vectors delivering Vglut3 were injected via the posterior semicircular canal (PSCC), with auditory brainstem response (ABR) thresholds and cochlear transgene expression assessed at days 1–14 post-injection. VGLUT3 expression in Vglut3KO mice revealed rapid transduction, detectable in inner hair cells (IHCs) by day 1, peaking at day 14. Remarkably, hearing recovery commenced as early as day 1 post-injection, and plateaued near wild-type (WT) levels by day 5. Functional correlation analysis demonstrated a robust inverse relationship between FLAG expression and hearing thresholds. This study provides critical insights into the dynamic processes underlying cochlear gene therapy and challenges the conventional paradigm that 1–2 weeks are required for functional recovery.